How the type of risk reduction influences required sample sizes in randomised clinical trials. Issue 11 (1st July 2004) - Bruynesteyn, K; Wanders, A; Landewé, R; van der Heijde, D
Abstract : To increase change between groups, randomised clinical trials (RCT) often include patients with high risk for a particular outcome, by inclusion criteria that select predictors for that outcome. This increases the statistical power, and fewer patients are required for that RCT. The way in which patient selection influences the power, and thus sample size required, depends on how an intervention reduces the individual risk: by an absolute or relative risk reduction model.